Glomerulonefritis C3 : una nueva categoría de glomerulonefritis con implicaciones etiopatogénicas (2015)
ABSTRACT: Glomerulonephritis with only deposits of C3 (GN-C3) could involve alteration on the complement alternative pathway. Objective: To describe retrospectively a series of GNC3 cases and to determine the frequency with which patients continue with renal alterations and/or hypocomplementemia. Methods: The 22 cases of GN-C3 diagnosed between 2004 and 2012 at the Department of Pathology, Faculty of Medicine, University of Antioquia (Medellin, Colombia) were included. Their histological and clinical characteristics and their outcome were evaluated. Results: 14 patients were children and 12 were males. Mean age was 13 years (range: 3-65). Ten presented as a nephritic syndrome, seven as a rapidly progressive GN, three as acute renal failure, one as chronic renal failure, and one as a nephrotic-nephritic syndrome. The C3 fraction of complement was low in 21 cases. All biopsies showed proliferative GN. There was complete remission in eight patients, persistent urinalysis alterations in four, chronic renal failure in six, five of them end-stage. No follow-up was done in four. In nine patients follow-up determination of C3 serum levels was done; in all of them they normalized between 1 to 3 months after biopsy. Conclusions: GN-C3 can produce persistent or recurrent kidney alterations and end-stage renal disease. Long-term follow-up with repeated determinations of C3 is advisable.